Urgensi Sosialisasi Pendidikan Dalam Merevitalisasi Semangat Belajar Siswa: Array - Selfi Lailiyatul Iftitah; Rika Susanti; Alfita Yuliana; Nur Adibah; Nafira Indriana; Syaiful Bahri; Moh Basori Alwi (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
Socialization is a process of learning about everything in life which includes language, norms, values, social systems, science, livelihoods, arts, religion, and others. This service activity is carried out in an effort to revitalize students' enthusiasm for learning so that students are motivated, as well as providing information about the importance of education. The purpose of this service activity is to increase the learning motivation of Tariqat Shufiyah MA students to raise awareness of the Urgency of Education and to raise awareness of the family in providing support for their children so they want to continue their education after graduating from MA. MA Tariqat Shufiyah students have knowledge and an overview of education. The method used in this activity is lecture and discussion. From the results of socialization activities about the importance of education, this provides benefits to students as an effort to increase motivation and interest in revitalizing the spirit of learning. The conclusion of this activity is the increased motivation of MA Tariqat Shufiyah students to continue their education to a higher level, the growing awareness of parents of students to provide support and opportunities for their children to continue their education to a higher level, students gain knowledge and an overview of education.